Metacognition in Science Learning: Bibliometric Analysis of Last Two Decades - Wirzal, Mohd Dzul Hakim; Halim, Nur Syakinah Abdul; Md Nordin, Nik Abdul Hadi; Bustam, Mohamad Azmi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
The main objective of this study was to map (1) the research of metacognition in science learning; (2) learning interventions used and metacognition’s key components that learned, integrated, and investigated; and (3) future research recommendations of metacognition research in science learning. We analyzed 438 scientific documents published in journals and books indexed in the Scopus database using VOSviewer software to visualize research trends and main keywords investigated of metacognition in science learning. The research findings show that research in the field of metacognition in science learning through the metacognition as attribution that integrated into learning interventions and as a learning outcome has increased in the last two decades. Scientific concepts understanding, critical thinking skills, motivation, and attention are the main goals in metacognition research. Inquiry-based learning, such as problem-based learning, is the most frequently used intervention to teach students metacognition. The research gaps found are (1) the cognitive regulations are the most investigated aspect, while cognitive aspects such as declarative knowledge, procedural knowledge, and conditional knowledge have not been widely investigated in science learning; (2) metacognition research on college students has a high frequency compared to school students; and (3) the integration of metacognition in online learning is still less investigated, this is indicated by the recommendations of several research results that encourage the integration of self-regulated learning into online learning.